Gambaran Body Image Pada Mahasiswa Pengguna TikTok di Universitas Nusa Cendana - Barek, Valentina Pradnya Ina; Keraf, M. K. P. Abdi; Takalapeta, Theodora (Innovative: Journal Of Social Science Research, 2025)
The growing popularity of TikTok among university students has brought about new dynamics in how individuals perceive their bodies. This study aims to describe body image among TikTok users at Nusa Cendana University. Using a qualitative approach with thematic analysis, data were collected through semi-structured interviews with five active TikTok users. The study identified six main themes: body perception, the influence of TikTok on self-view, responses to social criticism, local culture and values, motivations for content creation, and changes in self-perception. Findings reveal that although TikTok may trigger social comparison, it also fosters self-acceptance, confidence, and appreciation for body diversity. Local culture and social support play a significant role in shaping participants' experiences on the platform. In conclusion, TikTok has a complex role in shaping body image, with both positive and negative impacts depending on the users’ social and personal context.